Effect of injection pressure on performance and emission of diesel engine with blends of Honge-Rice bran bio diesel. (2021) - Suresh, K.V.; Fernandes, Peter; Raju, K.
Abstract: In this study the performance and emission tests were conducted on single cylinder 4 S diesel engine using Honge biodiesel and Rice bran methyl ester (RBO) blend with diesel. Two samples of bio diesel blends 10R5H (10% RBO + 5% Honge + 85% Diesel) and 20R5H (20% RBO + 5% Honge + 75% Diesel) were prepared and tested at different injection pressures such as 180 bar, 200 bar and 220 bar at 16.5 compression ratio with varied load and the results are compared with diesel at 220 bar injection pressure. The test results showed that at full load, the brake thermal efficiency of 20R5H is 33.32% which is close to diesel i.e. 34.36%. Honge and Rice bran hybrid biodiesel blends at 220 bar injection pressure exhibited better performance and low emission than at 180 bar injection pressures except NOx. Hence, the 20R5H optimized fuel blend can be considered for a compression ignition engine without any modification.